PERBANKAN SYARIAH DI INDONESIA DIPANDANG DARI SUDUT AGAMA, SEJARAH SERTA DASAR HUKUMNYA - Tuty Sariwulan (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
Abstract Indonesian Muslim community at this point will have a choice of a sound banking system and trusted to accommodate their needs for banking services, in line with Islamic principles based on the Qur'an and Hadith. With the rapid growth of Islamic banking in Indonesia, then it became clear that Islamic banks are desired by the majority of Muslim society in Indonesia. Characteristics of Islamic banking include: suppression of ongoing imposition of interest, limiting the unproductive speculative activity, financing is addressed to the lawful efforts in accordance with Islamic principles, and operating profit-sharing system. Determining the amount of profit sharing between the bank and the customer is based on the agreement in a written agreement between both parties. The main differences between conventional banking Islamic banking is the prohibition of riba (interest) for Islamic banking. Thus, the paying and receiving interest on money borrowed and lent prohibited. Furthermore, because the basis of operation is based on sharia, it was natural this institution is an alternative institution that is expected to eliminate the doubt, especially among Muslims. Keywords: Islamic Banking, History of Islamic Backing in Indonesia